Faktor-Faktor yang Memengaruhi Pilihan Karier Siswa SMK Negeri di Jakarta Selatan - Anisa Yasril; Agus Wibowo; Maulana Amirul Adha (Jurnal Ilmiah Ekonomi dan Manajemen Indonesia, 2026)
This study aims to analyze the effects of self-efficacy and achievement motivation on career choices among public vocational high school students in South Jakarta, with entrepreneurial intention as a mediating variable, based on the perspectives of the Theory of Reasoned Action (TRA) and the Theory of Planned Behavior (TPB), which emphasize the role of intention in shaping individual decisions and behavior. This study employed a quantitative survey approach involving 267 Grade XII students selected using proportional random sampling. Data were analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The results indicate that self-efficacy has a positive and significant effect on entrepreneurial intention (T = 7.792; p = 0.000) and career choice (T = 4.832; p = 0.000). Achievement motivation positively and significantly affects entrepreneurial intention (T = 6.915; p = 0.000) and career choice (T = 5.735; p = 0.000). Entrepreneurial intention positively and significantly affects career choice (T = 5.167; p = 0.000) and mediates the effects of self-efficacy (T = 3.881; p = 0.000) and achievement motivation (T = 3.610; p = 0.000) on career choice. The R² values are 26.6% for entrepreneurial intention and 57.9% for career choice. These findings support TRA and TPB by demonstrating that intention serves as a mechanism linking individual psychological factors to career choices, particularly entrepreneurship as a career alternative after graduation.